Formulasi Sediaan Gel dari Ekstrak Metanol Biji Alpukat (Persea americana Mill.) Sebagai Penyembuh Luka Sayat Pada Tikus Jantan (Rattus norvegicus) - Vera Estefania Kaban; Nasri Nasri; Hariyadi Dharmawan Syahputra; Raissa Fitri; Zulmai Rani; Muhammad Fauzan Lubis (Herbal Medicine Journal, 2022)
The avocado (Persea americana Mill.) is a fruit that is often found. This versatile fruit has many benefits for humans. The benefits of avocado are as anti-hyperlipidemic, analgesic, anti-inflammatory, anticonvulsant, hypoglycemic, hypercholesterolemic, wound healing and prevent cancer. The aims of this study was to make avocado seed methanol extract into a gel preparation and to determine the effect of avocado seed methanol extract gel and at what concentration the effective treatment for wounds in mice and its comparison with Star Ag gel as a positive control. The research was conducted using an experimental method. The manufacture of avocado seed methanol exstract was carried out by maceration method using methanol as a solvent. The result of the study were statistically analyzed using One Way Anova. The result of the data analysis at a concentration of 5% obtained a sig value <0,05. Based on One Way Anova analysis of the five treatments, the most effective was avocado seed methanol extract gel with a concentration of 5%.